Occupational epidemiological characteristics of noise-induced hearing loss and the impact of combined exposure to noise and dust on workers' hearing-a retrospective study - Bin Zhou; Jiaxiang Zhang (Frontiers Media S.A., 2024)
IntroductionThe aim of the study was to investigate the occupational epidemiological characteristics of hearing loss among noise-exposed workers through a cross-sectional study and to explore the impact of combined noise and dust exposure on workers' hearing loss through a longitudinal study.ResultsThis cross-sectional study revealed that the risk of speech-frequency hearing loss increases with age (OR = 1.096, 95%CI = 1.081-1.111). Independent factors influencing high-frequency hearing loss include sex, age, hazardous factors, industry category, and enterprise size. Scientific research and technical services (OR = 1.607, 95%CI = 1.111-2.324), wholesale and retail (OR = 2.144, 95%CI = 1.479-3.107), manufacturing (OR = 1.907, 95%CI = 1.429-2.545), and other industries (OR = 1.583, 95%CI = 1.002-2.502) are risk factors for high-frequency hearing loss, whereas being female (OR = 0.297, 95%CI = 0.236-0.373) is a protective factor against high-frequency hearing loss. Independent factors influencing occupational noise-induced hearing loss include sex, working age, hazardous factors, industry category, smoking, and drinking, with the risk of occupational noise-induced hearing loss increasing with working age (OR = 1.045, 95%CI = 1.031-1.058). Noise and dust work (OR = 1.271, 95%CI = 1.011-1.597), other work (OR = 0.619, 95%CI = 0.479-0.800), manufacturing (OR = 2.085, 95%CI = 1.336-3.254), other industries (OR = 2.063, 95%CI = 1.060-4.012), occasional smokers (OR = 0.863, 95%CI = 0.652-1.142), regular smokers (OR = 1.216, 95% CI = 0.987-1.497), and excessive drinkers (OR = 2.171, 95%CI = 1.476-3.193) are risk factors for occupational noise-induced hearing loss, whereas being female (OR = 0.496, 95%CI = 0.347-0.709) is a protective factor against occupational noise-induced hearing loss. The longitudinal study revealed differences in pure-tone hearing threshold test results at 500 Hz, 1,000 Hz, 3,000 Hz, 4,000 Hz, and 6,000 Hz in both ears before and after enrollment among noise-exposed workers (p < 0.05). Combined noise and dust exposure (OR = 4.660, 95%CI = 1.584-13.711), 1st year (OR = 1.540, 95%CI = 1.128-2.103), 2nd year (OR = 1.994, 95%CI = 1.409-2.821), and 3rd year (OR = 1.628, 95%CI = 1.170-2.264) were risk factors for high-frequency hearing loss.DiscussionCombined noise and dust exposure is a risk factor for occupational noise-induced hearing loss. Additionally, occupational noise-induced hearing loss is influenced by gender, working age, enterprise industry category, smoking, and drinking. Employers should enhance occupational health management and improve workers' occupational health literacy, with a particular focus on older male workers of long working age, and those with unhealthy habits. Combined exposure to noise and dust may have a synergistic effect on causing high-frequency hearing loss, and comprehensive protective measures should be implemented for workers exposed to both.